Combustion synthesis of TiC-based ceramic-metal composites with high entropy alloy binder. Issue 7 (July 2020) - Rogachev, A.S.; Vadchenko, S.G.; Kochetov, N.A.; Kovalev, D. Yu.; Kovalev, I.D.; Shchukin, A.S.; Gryadunov, A.N.; Baras, F.; Politano, O.
Abstract: Ceramic-metal composites TiC–High-Entropy Alloy (HEA) CoCrFeNi Me ( Me = Mn, Ti or Al) were first produced by combustion synthesis method. Self-sustained synthesis occurs due to heat release from exothermic reaction Ti + C = TiC; the binder content was varied between zero and 40–50 wt.%. The combustion velocity and temperature gradually decreased with increasing binder content. Resultant materials consist of TiC grains and two-phase ( fcc and bcc ) binder. Vickers microhardness (100 g) of compacted cermet materials with 30 wt.% of binder was in the range of 10–17 GPa and increased with increasing bcc to fcc ratio. Based on experimental results and thermodynamic calculations, the mechanism of microstructure formation in TiC–HEA cermets was suggested.